Respuesta :

Answer:

a = -0.5

Step-by-step explanation:

[tex] \rm Solve \: for \: a: \\ \rm \longrightarrow - \dfrac{1}{4}a - 4 = \dfrac{7}{4}a - 3 \\ \\ \rm Put \: each \: term \: in \: - \dfrac{1}{4}a - 4 \: over \: the \\ \rm common \: denominator \: 4: \\ \rm - \dfrac{a}{4} - 4 = - \dfrac{a}{4} - \dfrac{16}{4} : \\ \rm \longrightarrow - \dfrac{a}{4} - \dfrac{16}{4} = \dfrac{7}{4}a - 3 \\ \\ \rm - \dfrac{a}{4} - \dfrac{16}{4} = \dfrac{ - a - 16}{4} : \\ \rm \longrightarrow \dfrac{ - a - 16}{4} = \dfrac{7}{4}a - 3 \\ \\ \rm Put \: each \: term \: in \: \dfrac{7}{4}a - 3 \: over \: the \\ \rm common \: denominator \: 4: \\ \rm \dfrac{7a}{4} - 3 = \dfrac{7a}{4} - \dfrac{12}{4} : \\ \rm \longrightarrow \dfrac{ - a - 16}{4} = \dfrac{7a}{4} - \dfrac{12}{4} \\ \\ \rm \dfrac{7a}{4} - \dfrac{12}{4} = \frac{7a - 12}{4} : \\ \rm \longrightarrow \dfrac{ - a - 16}{4} = \dfrac{7a - 12}{4} \\ \\ \rm Multiply \: both \: sides \: by \: 4: \\ \rm \longrightarrow \dfrac{ - a - 16}{ \cancel{4}} \times \cancel{4}= \dfrac{7a - 12}{ \cancel{4}} \times \cancel{4} \\ \\ \rm \longrightarrow -a - 16 = 7 a - 12 \\ \\ \rm Subtract \: 7 a \: from \: both \: sides: \\ \rm \longrightarrow (-a - 7 a) - 16 = (7 a - 7 a) - 12 \\ \\ \rm -a - 7 a = -8 a: \\ \rm \longrightarrow -8 a - 16 = (7 a - 7 a) - 12 \\ \\ \rm 7 a - 7 a = 0: \\ \rm \longrightarrow -8 a - 16 = -12 \\ \\ \rm Add \: 16 \: to \: both \: sides: \\ \rm \longrightarrow (16 - 16) - 8 a = 16 - 12 \\ \\ \rm 16 - 16 = 0: \\ \rm \longrightarrow -8 a = 16 - 12 \\ \\ \rm 16 - 12 = 4: \\ \rm \longrightarrow -8 a = 4 \\ \\ \rm Divide \: both \: sides \: of \: -8 a = 4 \: by \: -8: \\ \rm \longrightarrow

\dfrac{ - 8a}{ - 8} = \dfrac{4}{ - 8} \\ \\ \rm \dfrac{ - 8}{ - 8} = 1: \\ \rm \longrightarrow a = - \dfrac{4}{ 8} \\ \\ \rm - \dfrac{4}{ 8} = - \dfrac{1}{2} : \\ \rm \longrightarrow a = - \dfrac{1}{2} \\ \\ \rm \longrightarrow a = - 0.5[/tex]

ACCESS MORE